1994
DOI: 10.1099/0022-1317-75-12-3477
|View full text |Cite
|
Sign up to set email alerts
|

Functional reconstitution in lipid vesicles of influenza virus M2 protein expressed by baculovirus: evidence for proton transfer activity

Abstract: The influenza virus M2 protein was expressed from a recombinant baculovirus in Spodoptera frugiperda Sf9 cells, purified and reconstituted into artificial membrane vesicles. The specific inhibitor amantadine overcame the toxic activity of the protein and boosted the rate of M2 synthesis by a factor of 10, allowing yields of about 1 mg of purified M2 protein per g of Sf9 cells. M2 protein expressed in this system was phosphorylated and palmitoylated and displayed properties similar to the authentic virus protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
4

Year Published

1997
1997
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 37 publications
4
53
0
4
Order By: Relevance
“…We showed that proton translocation into vesicles reconstituted with wild-type M2 protein was rimantadinesensitive while a rimantadine-resistant M2 variant exhibited resistance in this system (Schroeder et al, 1994). Recent electrophysiological measurements of rimantadine-sensitive proton currents in M2-expressing murine erythroleukaemia cells (Chizhmakov et al, 1996) confirm and extend these observations.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…We showed that proton translocation into vesicles reconstituted with wild-type M2 protein was rimantadinesensitive while a rimantadine-resistant M2 variant exhibited resistance in this system (Schroeder et al, 1994). Recent electrophysiological measurements of rimantadine-sensitive proton currents in M2-expressing murine erythroleukaemia cells (Chizhmakov et al, 1996) confirm and extend these observations.…”
Section: Introductionsupporting
confidence: 71%
“…The peptide and the sheep serum were purchased from Seramun. Protein purification was monitored by silver staining and Western blots (Schroeder et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations